APRIMORANDO COMPETÊNCIAS EM MEDICINA: O IMPACTO DAS TDIC’s NA COGNIÇÃO, HABILIDADES E ATITUDES DOS ACADÊMICOS - Lima Nunes , Karine; Ferreira da Cunha Santos , Mirella; Sarubbi Junior , Vicente (ANAIS DO ENIC, 2026)
-